2013
DOI: 10.3329/bjas.v41i2.14132
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of dairy farming technologies by small farm holders: practices and constraints

Abstract: In Bangladesh, usually, small scale farmers are not adopted to use all kinds of improved technologies in dairy farming. But, high level of technology adoption has a direct impact on milk yield and household's income generation as well as dairy development. The objectives of this study was to determine the causes of adoption and non adoption of high yielding breed, the level of practices and constraints in adopting the improved technologies. The study was carried out in three different agro-ecological zones and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
38
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 13 publications
16
38
0
3
Order By: Relevance
“…Suni tohumlama yaptıran ve yaptırmayan süt sığırcılığı işletmelerinde inek başına ortalama süt verimindeki fark istatistik açıdan anlamlı bulunmuştur (Çizelge 1). Yapılan benzer bir çalışmada, inek başına süt verimi suni tohumlama yaptıran ve yaptırmayan işletmelerde sırasıyla 9.2 kg, 2.3 kg olarak tespit edilmiştir (Quddus, 2012). Bu sonuçlara göre, suni tohumlama yaptıran işletmelerde inek başına ortalama süt veriminin suni tohumlama yaptırmayan işletmelere göre daha yüksek olduğu söylenebilir.…”
Section: Bulgular Ve Tartışmaunclassified
“…Suni tohumlama yaptıran ve yaptırmayan süt sığırcılığı işletmelerinde inek başına ortalama süt verimindeki fark istatistik açıdan anlamlı bulunmuştur (Çizelge 1). Yapılan benzer bir çalışmada, inek başına süt verimi suni tohumlama yaptıran ve yaptırmayan işletmelerde sırasıyla 9.2 kg, 2.3 kg olarak tespit edilmiştir (Quddus, 2012). Bu sonuçlara göre, suni tohumlama yaptıran işletmelerde inek başına ortalama süt veriminin suni tohumlama yaptırmayan işletmelere göre daha yüksek olduğu söylenebilir.…”
Section: Bulgular Ve Tartışmaunclassified
“…In a recent survey of Bangladeshi dairy farmers, three of the four most commonly cited reasons for not adopting crossbred cattle (1. high costs of inputs, 2. high Crossbreeding in developing countries price of feeding and 3. lack of money for purchasing animals) involved the economic capacity to purchase inputs. The fourth reason was the complexity of management and the additional investment in time (Quddus, 2012). Other smallholder survey in Ethiopia and Tanzania also showed that availability of capital and access to credit facilitate the implementation of crossbreeding (Abdulai and Huffman, 2005;Mekonnen et al, 2010) by smallholders.…”
Section: Socio-economic and Technical Factors Around Crossbreeding Bamentioning
confidence: 99%
“…Generally, most of the external reasons for the sustainability of a crossbreeding program can be linked to one or all of three interdependent factors, namely, the access to adequate Crossbreeding in developing countries stock, the opportunity of improved livestock to express its genetic potential and the efficiency of the market chain. The first prerequisite for the success of a given crossbreed program is that performance of crossbred animals must match farmer expectations, which helps ensure that smallholders have the motivation to implement or maintain crossbreeding within their farm (Quddus, 2012;Roschinsky et al, 2015).…”
Section: Socio-economic and Technical Factors Around Crossbreeding Bamentioning
confidence: 99%
See 1 more Smart Citation
“…Investment efforts and skills required in breeding and feeding programmes aiming to increase productivity and milk yield are often too intense for smallholders. A study by Quddus [29] proved that regardless of all the advantages of technology adoption to ensure better milk yield, smallholders' ability to adapt is not labile and is directly related to a lack of education, experience, and financial status and support services. Record keeping is a key management tool that measures dairy production and health status efficiency and improvement.…”
Section: Social Considerationsmentioning
confidence: 99%